Obliquity: Why Our Goals Are Best Achieved Indirectly - and Kay, John (Penguin Books, 2010)
"John Kay tells a fast-paced detective story as he searches for the surprising secret to success...Brilliant." -Tim Harford, author of The Logic of Life In this revolutionary book, economist John Kay proves a notion that feels at once paradoxical and deeply commonsensical: the best way to achieve any complex or broadly defined goal, from happiness to preventing forest fires, is the indirect way. We can learn how to achieve our objectives only through a gradual process of risk taking and discovery-what Kay calls obliquity. The author traces this seemingly counterintuitive path to success as it manifests itself in nearly every aspect of life, including business, politics, sports, and more.